2017
DOI: 10.3390/molecules22122081
|View full text |Cite|
|
Sign up to set email alerts
|

Fluorinated Analogs of Organosulfur Compounds from Garlic (Allium sativum): Synthesis, Chemistry and Anti-Angiogenesis and Antithrombotic Studies

Abstract: We describe the synthesis, reactivity, and antithrombotic and anti-angiogenesis activity of difluoroallicin (S-(2-fluoroallyl) 2-fluoroprop-2-ene-1-sulfinothioate) and S-2-fluoro-2-propenyl-l-cysteine, both easily prepared from commercially available 3-chloro-2-fluoroprop-1-ene, as well as the synthesis of 1,2-bis(2-fluoroallyl)disulfane, 5-fluoro-3-(1-fluorovinyl)-3,4-dihydro-1,2-dithiin, trifluoroajoene ((E,Z)-1-(2-fluoro-3-((2-fluoroallyl)sulfinyl)prop-1-en-1-yl)-2-(2-fluoroallyl)disulfane), and a bis(2-flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 40 publications
0
20
0
1
Order By: Relevance
“…The amino acid composition analysis results of GP, GPH-P, and GPH-T are shown in Leu, Gly residues, and C-terminal peptides with Arg, Tyr, Phe, and Pro residues have significant antihypertensive effects (Block et al, 2017;Girgih, He, & Aluko, 2014;Tu, Wang, et al, 2018). According to the proportion of these kinds of amino acids in GPH-P and GPH-T, GP hydrolyzed with appropriate enzymes could…”
Section: Amino Acids Compositional Analysis Of Gp Gph-p and Gph-tmentioning
confidence: 99%
“…The amino acid composition analysis results of GP, GPH-P, and GPH-T are shown in Leu, Gly residues, and C-terminal peptides with Arg, Tyr, Phe, and Pro residues have significant antihypertensive effects (Block et al, 2017;Girgih, He, & Aluko, 2014;Tu, Wang, et al, 2018). According to the proportion of these kinds of amino acids in GPH-P and GPH-T, GP hydrolyzed with appropriate enzymes could…”
Section: Amino Acids Compositional Analysis Of Gp Gph-p and Gph-tmentioning
confidence: 99%
“…Research has revealed that allicin targets multiple pathways implied in the inhibition of cancer development [27], including cell cycle arrest [21,28], the induction of apoptosis [29][30][31][32][33][34], the induction of histone acetylation [35] and the inhibition of angiogenesis [36]. Some of these studies dealing with the induction of apoptosis by allicin have also been reported for Caco-2 and HT-29 [20,34,37].…”
Section: Discussionmentioning
confidence: 99%
“…berichteten über die biomimetische thermische Umlagerung von Allicin in wässrigem Aceton (Schema ) . Kürzlich wurde diese Synthese zu einem trifluorierten Analogon erweitert . Obwohl die Synthese eine Eintopfreaktion darstellt, ist die Ausbeute mit 34 % recht niedrig.…”
Section: Methodsunclassified